EKSPLORASI PENGALAMAN BELAJAR GERAK DASAR PADA MASA PERTUMBUHAN PESAT ANAK USIA 6–8 TAHUN: STUDI FENOMENOLOGI DI SEKOLAH DASAR NEGERI 064976 MEDAN - Deon Alfredo Purba; Wahyu Maulana Manik; Denilson Requelme Simbolon; Titi Kamal Nababan; Ronauli Gultom; Amansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT The age of 6–8 years is a rapid growth phase marked by neuromuscular coordination acceleration and intensive nerve myelination. At this phase, mastery of fundamental movement skills (FMS) encompassing locomotor, non-locomotor, and manipulative skills lays the foundation for lifelong sports ability and active lifestyle. However, existing research mostly measures motor achievement quantitatively and neglects the subjective experiential dimension of children themselves. This study aims to explore and interpret the essential structure of FMS learning experiences from the perspective of 6–8-year-old children at SDN 064976 Medan through a transcendental phenomenological qualitative approach (Moustakas, 1994). The study involved eight participants (Grade 1–2 students) purposively selected based on rapid growth criteria, communication ability, and parental consent. Data were collected through activity-based semi-structured interviews, participatory observation, and drawing-telling technique. Data analysis followed Moustakas procedures: epoche, horizontalization, meaning clustering, theme formation, and textural-structural descriptions toward essence synthesis. Findings produced four essential themes: (1) The Newly Discovered Body - children experience surprise over new abilities accompanied by awareness of physical change; (2) Movement as Structured Free Play - the need for spontaneity negotiates with formal instruction, creating flow experience when activities are packaged as games; (3) Social Interaction Drives Enthusiasm - peer imitation, competition, and cooperation become the motor of movement motivation; and (4) Obstacles and Injuries as Signs of Effort - falling and fatigue are positively interpreted as evidence of genuine effort. The essence of FMS learning experience is a journey of discovering a new physical identity mediated by the joy of play, social interaction, and negotiation between the limitations and potential of the changing body.